Galant – new sort of tomato for the Far East - Galina A. Kuzmitskaya (Овощи России)
Relevance. Tomato is one of the most spreaded vegetable cultures in Khabarovsk Territory. Presence of the favourable weather conditions in the region, high ecological plasticity of tomato sorts promote the tomato cultivation in open and protected ground everywhere and in large areas. The main cause of crop failure or large losses of tomatoes in the Far East is a complex, unpredictable, not meeting anywhere else in Russia the monsoon climate causing a strong waterlogging observed almost every year in July-August, the period of the main tomato harvest forming. Such weather conditions promote the development of main diseases of the solanaceous cultures, and their most aggressive races often appear. Therefore a high natural infectious background and a sharply variable hydrothermal regime are the main limiting factors in the cultivation of tomatoes in the Khabarovsk Territory.Methods. Work on the creation of a new variety with the given parameters was started in 2007 by conducting intervarietal crossings between Volgogradsky 5/95 and Zarya Vostoka varieties, followed by multiple selections against a natural infectious background. The early ripening variety of Zarya Vostoka is a local selection variety, was used in the breeding process as an early maturity donor, and Volgogradsky 5/95, a stem type of plant. The main method of breeding work to create new varieties of tomato was analytical with continuous selection. All the necessary phenological, biometric and phytopathological observations and counts according to methods generally accepted in this culture. The purpose of our research was to create a new strain tomato variety with a short period of vegetation, forming the harvest of fruit before the appearance and spread of the disease and high productive potential.Results. This publication presents the information about the new local tomato sort Galant. This sort was received by inter-sort hybridization between the stem sort Volgogradsky 5/95 and local early ripening sort Zarya Vostoka. The sort was selected as a result long-term selection on the natural infectious background with the assessment by progeny of promising lines for a complex of morpho-biological and economically valuable traits in monsoon climate conditions of Priamurye. The new sort is different from other studied non-district and local sorts by fastripeness, high productivity, resistance to main diseases and also by stem type of plant.